Geotechnical effects of polymer treatment on tailings – state of knowledge review - Reid, D; Fourie, AB (Paste 2018: 21st International Seminar on Paste and Thickened Tailings, 2018)
As the trialling and application of polymer treatment of tailings at the point of discharge has increased, so have studies to assess the effects of polymer treatment on subsequent tailings geotechnical behaviour. A review of the publically available studies is presented, including laboratory and in situ tests on mature fine tailings, comparison of consolidation tests on a range of tailings types, and a large comparative study on a synthetic tailings that included laboratory and cone penetrometer testing. The data available indicate that polymer treatment can have significant effects, including changes to rate of consolidation, density of a material at a given effective stress, location of critical state line, undrained shear strength at a given density, and strain rate effects. Also, while there are less data on this topic, there is evidence that shearing, and some forms of ageing, can reduce the effects of polymer treatment on geotechnical properties. Penetrometer test comparisons indicate that the increased rate of consolidation for polymer-treated material can result in quite different penetrometer responses owing to drainage effects.
Keywords: inline flocculation; polymer treatment; consolidation; undrained strength